New and future developments in microbial biotechnology and bioengineering : phytomicrobiome for sustainable agriculture - Verma, Jay Prakash; Macdonald, Catriona; Gupta, Vijai Kumar; Podile, Appa Rao (Elsevier, 2021)
New and Future Developments in Microbial Biotechnology and Bioengineering: Phytomicrobiome for Sustainable Agriculture provides a comprehensive overview of the phytomicrobiome and a holistic approach for its various mechanisms, including plant growth, nutrient content, crop yield improvement, soil fertility, and health management. This book explores the genus- and species-specific endophytic microbes for developing an efficient indigenous microbial consortium for enhancing the productivity of sustainable agriculture. An essential resource for students, researchers, and scientists in the fields of biotechnology, microbiology, agronomy, and the plant protection sciences, New and Future Developments in Microbial Biotechnology and Bioengineering: Phytomicrobiome for Sustainable Agriculture highlights the plant growth-promoting activities of the phytomicrobiome and focuses on both its basic and applied aspects and the significant role they play in plant protection.